Defying the 'Juncker Curse' : can reformist governments be re-elected - Buti, Marco; Turrini, Alessandro 1966-; Noord, Paul van den.; Biroli, Pietro; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : European Comission : Directorate-General for Economic and Financial Affairs, 2008)
European policy makers, notably in the euro area, seem to take for granted that the electorate will punish them for bold reform in product and labour markets. This may explain why progress in the euro area has been comparatively limited. This paper posits and, using a dataset for 21 OECD countries, shows that this fear of electoral backlashes is unfounded, provided that financial markets work well. The mechanisms involved are relatively straightforward: well functioning financial markets "bring forward" future yields of structural reform to the present, thus permitting to overcome possible short-run costs. As a result, the electorate tend to reward, not punish, reformist governments. This has important implications for the design of structural reform packages, with financial market reforms being an essential ingredient beside product and labour market reforms.
Economic Papers.